Young People Participating in Recreational ActivitiesAccording to Different Variables Examining Their Attitudes Towards Physical Education Lessons - ŞİRİN, Ercan (International Journal of Holistic Health, Sports and Recreation, 2023)
The aim of the study was to examine the attitudes of young people who participate in youth and sports activities recreationally towards physical education lessons. Among the quantitative research models, the relational survey model was used within the scope of general survey research. The population of the research consists of young people at high school level. The sample group consisted of a total of 574 high school students, 276 female and 298 male, studying in high schools in Kütahya. 171 of the students are studying in vocational high schools, 168 in anatolian high schools and 235 in fine arts high schools. The sample group was determined using random selection technique. In the study, a personal information form consisting of 7 items and the attitude scale of second grade students towards physical education course developed by Kır (2012) were used. The scale is a 5-point Likert type scale consisting of 20 items. The total reliability (Cronbach Alpha) value of the scale was found to be 0.871. Evaluations were made based on total values. A normality test was applied to the data obtained, and since the skewness and kurtosis values were between -3 and + 3, it was accepted that the assumption of normality was met. In this context, independent samples t test, one-way analysis of variance and Welch test results were evaluated for hypothesis analysis. When the attitudes of individuals participating in recreational activities towards physical education and sports lessons were compared according to the gender variable, it was determined that men had a more positive attitude than women, there was a statistically significant difference according to the age variable, and the attitudes of young people towards physical education and sports classes at schools were at an average level. In addition, it was determined that the rate of vocational high school students was higher than other students according to the school type variable.